Effects of vitrification and the superovulated environment on placental function and fetal growth in an IVF mouse model. (26th July 2020) - Roeca, C; Silva, E; Barentsen, C; Powell, T L; Jansson, T
Abstract: In studies of human IVF, as compared to frozen embryo transfer (ET), fresh ET is associated with smaller infants and higher risk of small for gestational age infants. Recent observations suggest that ET using vitrified embryos is associated with higher pregnancy and live birth rates compared to fresh ET, but increased rates of large for gestational age infants. The mechanisms underlying these associations are largely unknown, and available evidence suggests that the influence of IVF, vitrification and the superovulated (SO) uterine environment on placental function and fetal growth is complex. This warrants further investigation given the prevalent practice in human IVF of both fresh ET into a SO uterine environment, and vitrification with ET into a more physiologic uterine environment. Using a mouse model that closely resembles human IVF, we investigated if vitrification of IVF embryos better preserves placental function and results in better pregnancy outcomes as compared to fresh ET because of transfer into a more physiologic endometrium. We found that the SO environment, independent of vitrification status, reduced implantation rates, inhibited placental mechanistic target of rapamycin signaling and induced placental stress signaling, resulting in fetal growth restriction (1.080 ± 0.05 g estrous fresh (n = 17 litters), 1.176 ± 0.05 g estrous vitrified (n = 12), 0.771 ± 0.06 g SO fresh (n = 15), 0.895 ± 0.08 g SO vitrified (n = 10), P < 0.0001). In addition, our study suggests that vitrification impairs the developmental potential of IVF blastocysts that resulted in a significantly smaller litter size (2.6 ± 2.3 fresh estrous vs 2.5 ± 2.4 fresh SO vs 1.6 ± 1.7 estrous vitrified vs 1.7 ± 1.8 SO vitrified, P = 0.019), with no effect on fetal growth or placental function at term. Our findings suggest that vitrification may negatively impact early embryonic viability, while the SO maternal uterine environment impairs both placental development and fetal growth in IVF.